Adaptation of Green Banking Practices in Commercial Banks of Nepal - Mishra, Puja (Apex Journal of Business and Management, 2023)
This research project aimed to investigate the current state of green banking practices along with the factors influencing the adoption in commercial banks in Nepal. The findings from the data analyzed through SPSS software revealed the descriptive findings indicate that among the five independent variables, Brand Image has the highest mean value of 3.596, indicating that it is perceived as the most important factor influencing the adoption of green banking practices. This is followed by Financial Benefits with a mean of 3.462, Regulatory Policies with a mean of 3.338, Environmental Interest with a mean of 3.332, and Stakeholder's Demand with the lowest mean of 3.076.Furthermore, the dependent variable, Adoption of Green Banking Practices, has a mean of 3.382, suggesting that respondents agree that the adoption of green banking practices is influenced by the independent variables, including Stakeholder's Demand, Regulatory Policies, Environmental Interest, Financial Benefits, and Brand Image. The study highlighted the importance of brand image as the most influential factor, with the highest mean score among the variables examined. Additionally, it indicated that there was a moderately positive environment for green banking practices among Nepalese commercial banks. Overall, this study contributes to the growing body of knowledge on green banking adoption and offers practical implications for sustainable banking practices in Nepal.